ANALISIS YURIDIS TERHADAP KAWIN BATAMBUAH YANG DILAKUKAN OLEH MASYARAKAT ADAT MINANGKABAU DI KABUPATEN AGAM SUMATERA BARAT - ARIEF BUDIMAN (PREMISE LAW JURNAL, 2016)
Adat (customary) law in Indonesia generally recognizes polygamy system among the adat sovereignties and peers in several regions. In Minangkabau, this system is known as ‘kawin batambuah’(making more wives) since adat and religion permit a man to get married with 4 women so that some people consider it as a token of pride and fame. The research was conducted in Agam District, West Sumatera, where ‘kawin batambuah’ still exists. The samples consisted of 3 subdistricts: Ampek Angkek Subdistrict, Kamang Magek Subdistrict, and Canduang Subdistrict in Agam District, taken by using random sampling technique. The result of the research shows that the implementation of ‘kawin batabuah’ is only performed in religious manner which has the impact on the children, the wives, and the joint property. The impact on the children is that they are only the children of their mother without the responsibility of the father. The impact on the wives is that they do not get any fairness since the husbands tend to love their younger wives than the old ones. The impact on the joint property is that it will belong to the wives since their husbands are only ‘sumando’/visitors to their ‘rumah gadang’ so that it is difficult to contribute the property since the marriage is based on religion. In Islam, polygamy is permitted on condition that the wives are not more than 4 although in Agam District some men have more than 4 wives. Keywords: Polygamy, Kawin Batambuah